2018
DOI: 10.3390/molecules23040948
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Composition and Content in Rye Plants with Different Grain Color

Abstract: The color of grain in cereals is determined mainly by anthocyanin pigments. A large level of genetic diversity for anthocyanin content and composition in the grain of different species was observed. In rye, recessive mutations in six genes (vi1...vi6) lead to the absence of anthocyanins in all parts of the plant. Moreover, dominant genes of anthocyanin synthesis in aleurone (gene C) and pericarp (gene Vs) also affect the color of the grain. Reverse phase high-performance liquid chromatography and mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…For example, we observed the presence of the MbHF35 orthologues at a linked genetic location on chromosome 7R in rye. This is in accord with reports that blue aleurone in rye requires the dominant alleles at six loci ( vi1–vi6 ), with vi1 mapping to chromosome 7R (Voylokov et al , ; Zykin et al , ). Further studies are needed to verify whether vi1 corresponds to the MbHF35 homologues identified in rye.…”
Section: Discussionsupporting
confidence: 90%
“…For example, we observed the presence of the MbHF35 orthologues at a linked genetic location on chromosome 7R in rye. This is in accord with reports that blue aleurone in rye requires the dominant alleles at six loci ( vi1–vi6 ), with vi1 mapping to chromosome 7R (Voylokov et al , ; Zykin et al , ). Further studies are needed to verify whether vi1 corresponds to the MbHF35 homologues identified in rye.…”
Section: Discussionsupporting
confidence: 90%
“…Dańkowskie Złote (a* = 4.24) and KWS Bono (a* = 3.29), but it did not differ significantly from the reference rye in the value of the b* (19.04). According to Zykin et al ( 2018 ), the color of cereal grain is determined mainly by the content of anthocyanin pigments.…”
Section: Resultsmentioning
confidence: 99%
“…In many recent literature reports, it had indeed been shown that an array of responses involving signal transduction systems and molecules with influence on tight regulation of biosynthetic pathway(s) could be characterized in different plant species, genotype or cultivars due to ecotype and genetic component-dependent variations response to the stress or defense response function during growth condition(s) of plants. This influences SM, depending on the season, environmental or external triggers [8, 22, 26, 73]. For example, production of essential oils in the trichome of leaves imply their defensive role against herbivores or insect predators while tannins production in the vacuoles of leaves cells located beneath epidermal surface and their bitter taste deter predators [73, 88].…”
Section: Introductionmentioning
confidence: 99%